Treatment of patients at high risk of osteoporotic fracture in a USF: the importance of FRAX®Port (Portuguese Journal of Family Medicine and General Practice, 2025)
Introduction: Osteoporosis is a bone disease whose prevalence has been increasing, particularly in elderly females. The main clinical consequence is the fragility fracture, leading to increased morbidity and mortality, and a decreased quality of life for the patient, representing a significant socioeconomic burden. The current challenge is the early identification of individuals at higher risk of fracture who require therapeutic intervention to prevent future fractures.Objectives: To study the beginning of anti-osteoporotic therapy in female patients at high risk of osteoporotic fracture.Methods: A cross-sectional study based on the review of medical records and telephone interviews of 50-year-old and older female patients from a Family Health Unit in the Western Lisbon area. The sample size was calculated using the SurveyMonkey website, and the population sample was randomly selected. Fracture risk was calculated using FRAX®Port. The population was stratified based on fracture risk, and therapy initiation was verified in high-risk patients.Results: A sample of 250 patients was obtained, of which 20.8% (n=52) had a high risk of fracture, 9.2% (n=23) had intermediate fracture risk, and 70% (n=175) had low fracture risk, according to FRAX calculation. Among the patients identified as having a high risk of fracture, 28.8% (n=15) were receiving anti-osteoporotic therapy.Conclusion: It was found that only 28.8% of patients at high risk of fracture were receiving treatment, highlighting the importance of raising awareness among healthcare professionals for the assessment of osteoporotic fracture risk in Family Medicine appointments and implementing a change in the diagnostic and therapeutic approach to osteoporosis.
Keywords: Osteoporosis; Osteoporotic fractures; Fracture risk; FRAX; Anti-osteoporotic therapy